Propuesta para el diseño de una ruta turística en el corredor las peñas – la tola, provincia de Esmeraldas. - Morales Oviedo, Carlos (2009)
This study is making a 21Km. tourist route divided by land and river sections that bring together some tourist attractions. The route starts in the zone’s best attraction, specifically Las Peñas beach, which receives the most visitors. Sustaining the argument the visitors would be motivated to visit the surrounding attractions, this research try to provide a concept to the zone composed by four places, which are El Majagual, Olmedo, La Tola and La Tolita Pampa de Oro, where the participation of the communities is also thought. The design of the route was reached throw three sequential steps divided in two chapters, first a tourist diagnostic of the chosen places, which aims to bring an actual view of the tourist situation, including tourist infrastructure, market and community. The diagnostic was analyzed, giving ideas to build strategies to promote the enclosure of the communities and proposals to be followed according to the tested sources all over the trail. The result was an offer created down a route image accessible in several spreading elements to be had by the tourists.